High-risk human papillomavirus: prevalence, association with clinical and morphological characteristics of invasive cervical cancer - L. S. Mkrtchian; V. I. Kiseleva; B. V. Boyko; L. I. Krikunova; V. A. Petrov; V. R. Gusarova; S. A. Ivanov; A. D. Kaprin; I. A. Zamulaeva (Исследования и практика в медицине)
Purpose of the study. Analysis of contemporary literature sources dedicated to the study of characteristics of high oncogenic risk human papillomavirus (HPV), associative links of the virus’s molecular-genetic parameters with the clinical and morphological characteristics of invasive cervical cancer (ICC).Materials and methods. A literature search was conducted in electronic databases including the National Center for Biotechnology Information Search database (PubMed/Medline), ResearchGate, Scopus, Web of Science, Cancer Tomorrow, Global cancer observatory, Cochrane Library, eLIBRARY, DisserCat. The search covered the period from 1990 to 2022 and utilized keywords in Russian and their English translations: cervical cancer, high oncogenic risk HPV, HPV status, HPV genotype, multiple infections, DNA integration, viral load. More than 120 full-text sources were studied, in which the analysis of possible correlations between the parameters of human papillomavirus infection and the clinical and morphological characteristics of cervical cancer was carried out. In review included data from 57 publications.Results. According to most authors, more than 88 % of patients with invasive ICC are HPV-infected. The etiological structure is dominated by HPV 16 (70–72 %), 18 (13–15 %), and 45 (5–7 %) types. Non-detection of HPV HR in cervical cancer is associated, including with a false negative result of the study.The literature analysis showed the presence of an association between HPV status and age, morphological form of the tumor, viral load, high oncogenic risk HPV genotype, presence of deep stromal invasion, and metastatic involvement of lymph nodes. With regard to such molecular genetic parameters of HPV HR as viral load and HPV DNA integration, associative relationship with prognostic important clinical indicators of cervical tumor – the stage of the disease, the loco-regional prevalence of the tumor process, the histological type of tumor – remains the subject of discussion.Conclusion. Many publications report a correlative link between HPV status and high oncogenic risk HPV genotype with such an important factor affecting ICC treatment outcomes as the morphological form of the tumor. Ambiguous conclusions on the presence of an association between a number of molecular-genetic parameters of HPV infection with the main prognostic factor – stage of the disease (due to the heterogeneity of samples, the use of different test systems, and the insufficiently complete account of the main parameters of HPV infection, especially data on viral DNA integration), make it advisable to conduct further research on a representative group of patients with homogeneous diagnostic protocols to determine the most complete spectrum of parameters of high oncogenic risk HPV. In addition, the conducted literature analysis showed the promise of searching for predictors of the effectiveness of specialized treatment of patients with ICC among such HPV infection parameters as HPV status, high oncogenic risk HPV genotype, and the significantly associated physical status of viral DNA.